The politics of exporting higher education: Russian university branch campuses in the “Near Abroad” - Chankseliani, M (Taylor & Francis, 2020)
This exploratory study represents the first attempt at examining the politics of exporting Russian higher education to the former Soviet countries. The existing numeric and narrative evidence on Russian universities’ international branch campuses (IBCs) was gathered and systematically organized in a new dataset. The study finds that the majority of IBCs operating in former Soviet countries are branches of Russian universities. While the effectiveness of these IBCs is difficult to demonstrate, the study suggests that the Russian Federation uses IBCs as a tool to retain and strengthen its political power and influence in the region. This is done through a nuanced exploration of the niche of Russian IBCs within the differentiated higher educational landscape and through the analysis of the Russian state’s political rationale for establishing and supporting Russian IBCs. The study proposes to interpret the politics of exporting Russian higher education using the frameworks of neo-imperialism and internationalization.